2017
DOI: 10.3928/00989134-20170811-04
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Providing Safe Mouth Care and Collecting Oral and Fecal Microbiome Samples from Nursing Home Residents with Dysphagia: Proof of Concept Study

Abstract: Individuals with dysphagia who reside in nursing homes often receive inadequate mouth care and experience poor oral health. From a policy perspective, the combination of absent evidence-based mouth care protocols coupled with insufficient dental coverage create a pool of individuals at great risk for preventable infectious illnesses that contribute to high health care costs. The purpose of the current study was to determine (a) the safety of a mouth care protocol tailored for individuals with dysphagia residin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Due to the heterogeneity of the included studies reviewed, the intervention categories are broad with some overlap. Three studies described a feeding intervention [32,38,41], two studies focused on oral hygiene [40,42], two studies on stimulation (taste and smell) [30,31], two studies on training [28,29], two studies on a caregiver algorithm [35,36], [43], one study focused on teaching the residents compensatory strategies [37], one study focused on mobilization of the spine [33], and one study focused on positioning, oral hygiene, and teaching swallowing techniques [34].…”
Section: Chen L L Et Al 2016 [38] Chinamentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the heterogeneity of the included studies reviewed, the intervention categories are broad with some overlap. Three studies described a feeding intervention [32,38,41], two studies focused on oral hygiene [40,42], two studies on stimulation (taste and smell) [30,31], two studies on training [28,29], two studies on a caregiver algorithm [35,36], [43], one study focused on teaching the residents compensatory strategies [37], one study focused on mobilization of the spine [33], and one study focused on positioning, oral hygiene, and teaching swallowing techniques [34].…”
Section: Chen L L Et Al 2016 [38] Chinamentioning
confidence: 99%
“…In two studies, the focus was on oral hygiene [39,40]. A controlled clinical trial evaluated the effect of adding a 0.05% chlorhexidine-containing solution to daily oral hygiene care, but no significant difference in the incidence of pneumonia was documented [39].…”
Section: Oral Hygienementioning
confidence: 99%
See 1 more Smart Citation
“…Nursing home research, especially research conducted by doctorally-prepared nurses, is in its infancy in Turkey. We opted, for this study, to exclude cognitively impaired residents due to systemimposed barriers for obtaining consent from family members or legally-authorized representatives, as is routinely done in the United States 28,32 . The primary author plans to repeat aspects of this study and including cognitively-impaired nursing home residents.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Kappa statistic and percent agreement, OHAT evaluation showed a moderate, substantial and almost perfect agreement between the evaluations by nurse 1 and nurse 2. It was showed that kappa statistics being considered moderate of OHAT Portuguese and Japanese versions [31][32] .…”
Section: Discussionmentioning
confidence: 99%